Diverse drug delivery systems for the enhancement of cancer immunotherapy: an overview - Liu, Xu; Cheng, Yang; Mu, Yao; Zhang, Zhaohan; Tian, Dan; Liu, Yunpeng; Hu, Xuejun; Wen, Ti (Frontiers in Immunology, 2024)
Despite the clear benefits demonstrated by immunotherapy, there is still an inevitable off-target effect resulting in serious adverse immune reactions. In recent years, the research and development of Drug Delivery System (DDS) has received increased prominence. In decades of development, DDS has demonstrated the ability to deliver drugs in a precisely targeted manner to mitigate side effects and has the advantages of flexible control of drug release, improved pharmacokinetics, and drug distribution. Therefore, we consider that combining cancer immunotherapy with DDS can enhance the anti-tumor ability. In this paper, we provide an overview of the latest drug delivery strategies in cancer immunotherapy and briefly introduce the characteristics of DDS based on nano-carriers (liposomes, polymer nano-micelles, mesoporous silica, extracellular vesicles, etc.) and coupling technology (ADCs, PDCs and targeted protein degradation). Our aim is to show readers a variety of drug delivery platforms under different immune mechanisms, and analyze their advantages and limitations, to provide more superior and accurate targeting strategies for cancer immunotherapy.